Transgenic Crops - Emerging Trends and Future Perspectives 2019
DOI: 10.5772/intechopen.78773
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Plant Genotype, Culture Medium andAgrobacteriumon Soybean Plantlets Regeneration during Genetic Transformation

Abstract: An efficient and reproducible plant regeneration protocol is essential for genetic manipulation of important crops in vitro through Agrobacterium-mediated genetic transformation. However, the establishment of such a procedure for recalcitrant legumes like soybean is still a major challenge. Genotype specificity, culture conditions and inefficient recovery of transgenic microshoots are some of the most important factors which requires optimisation before an efficient system of regeneration can be developed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Despite an abundance of protocols, approaches and attempts at improving genetic transformation of soybean, it is still considered a recalcitrant species (Xu et al 2022). Successful transformation of soybean with A. tumefaciens depends on factors such as culture medium, plant genotype, type of explant, bacterial strain and density, and their interaction (Mangena 2019). Rojas et al (2018) reported the transformation of two Colombian soybean varieties with a codon-optimized version of the A. tumefaciens cp4epsps gene using only elements in the public domain and showed the importance of the plant genotype and strain specificity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite an abundance of protocols, approaches and attempts at improving genetic transformation of soybean, it is still considered a recalcitrant species (Xu et al 2022). Successful transformation of soybean with A. tumefaciens depends on factors such as culture medium, plant genotype, type of explant, bacterial strain and density, and their interaction (Mangena 2019). Rojas et al (2018) reported the transformation of two Colombian soybean varieties with a codon-optimized version of the A. tumefaciens cp4epsps gene using only elements in the public domain and showed the importance of the plant genotype and strain specificity.…”
Section: Resultsmentioning
confidence: 99%
“…Soybean is considered a recalcitrant species for genetic transformation mediated by A. tumefaciens due to constraining factors that need to be optimized such as the specific interaction between plant genotype and bacterial strain, plant variety dependent regeneration, toxicity of antibiotics, A. tumefaciens overgrowth, in vitro selection and explant type, among others (Mangena 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The vulnerabilities of children of ward 14 of Bikita District due to climate change are in sharp contrasts of the social justice value of Ubuntu or Hunhu philosophy. Social justice is based on the principle of fairness, love, compassion, equality, genuineness among others (Mangena 2012). Such principles are part of the Ubuntu or Hunhu philosophy (Mangena 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Social justice is based on the principle of fairness, love, compassion, equality, genuineness among others (Mangena 2012). Such principles are part of the Ubuntu or Hunhu philosophy (Mangena 2012). There is social injustice when children drop out of school, engage in substance abuse, being victims or survivors of child marriages or child labour among others.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported that the A. rhizogenes -mediated transformation system could have been the cause of low transformation efficiency observed in soybean (Li et al, 2019 ; Bai et al, 2020 ; Zhang et al, 2020a ), rice (Butt et al, 2017 ; Usman et al, 2021 ), and tomato (Ron et al, 2014 ) genome editing. Varying culture conditions can also influence the infection and regeneration rates of the Agrobacterium- infected explants, which affects the reproducibility of the results obtained (Hamada et al, 2018 ) as observed in soybean (Li et al, 2017; Hada, 2018 ; Mangena, 2018 ), clover ( Trifolium subterraneum L.) (Rojo, 2021 ), and cassava (Nyaboga et al, 2015 ). This further showed inconsistencies observed in transformation efficiency through Agrobacterium mediated delivery.…”
Section: Introductionmentioning
confidence: 99%